2017
DOI: 10.22256/pubvet.v11n8.767-770
|View full text |Cite
|
Sign up to set email alerts
|

Anatomia macroscópica dos órgãos reprodutores do Puma yagouaroundi (Geoffroy, 1803) macho

Abstract: Puma yagouaroundi (gato-mourisco) é um felino que apresenta vasta distribuição geográfica no Brasil, podendo ser encontrado em vários biomas. Na literatura observa-se escassez de trabalhos sobre sua anatomia macroscópica. O objetivo do trabalho foi a descrição macroscópica do sistema reprodutor masculino visando a obtenção de informações que possam ser úteis ao manejo reprodutivo da espécie. O estudo foi realizado em um cadáver macho doado ao Laboratório de Anatomia Veterinária pelo Hospital Veterinário da Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…It was also observed that the epididymis is composed of smooth muscle and a cylindrical pseudo-stratified epithelium, similar to other mammalian species (Wick and Kress, 2002;Banks, 1992;Junqueira and Carneiro, 2015). Our findings on the prostate and bulbourethral glands of Leopardus pardalis complement the findings of Carneiro et al (2010) for the oncilla (Leopardus tigrinus) and Puma yaguaroundii (Rocha et al, 2017). Microscopically, it was possible to observe the internal epithelial layer as well as the prostatic concretion, similar to the findings of Wick and Kress (2002) and Junqueira and Carneiro (2015).…”
Section: Male Reproductive System Of the Ocelotsupporting
confidence: 91%
See 3 more Smart Citations
“…It was also observed that the epididymis is composed of smooth muscle and a cylindrical pseudo-stratified epithelium, similar to other mammalian species (Wick and Kress, 2002;Banks, 1992;Junqueira and Carneiro, 2015). Our findings on the prostate and bulbourethral glands of Leopardus pardalis complement the findings of Carneiro et al (2010) for the oncilla (Leopardus tigrinus) and Puma yaguaroundii (Rocha et al, 2017). Microscopically, it was possible to observe the internal epithelial layer as well as the prostatic concretion, similar to the findings of Wick and Kress (2002) and Junqueira and Carneiro (2015).…”
Section: Male Reproductive System Of the Ocelotsupporting
confidence: 91%
“…A macroscopic description of the male reproductive system of Leopardus pardalis was previously given by Carneiro et al (2010) , as the penis, scrotum, testis, epididymis, vas deferens and accessory genital glands such as a bulbourethral gland and prostate are present, but not the vesicular glands. The latter are also absent in domestic cats ( Godinho, 1999 ; Dyce et al, 2010 ) and in wild species as Puma yaguaroundii ( Rocha et al, 2017 ). Leopardus pardalis has relatively small testes ( Sarti, 2006 ; Carneiro et al, 2010 ) with the same anatomy as puma ( Puma concolor ) ( Mansfield and Land, 2002 ; Guião-Leite, 2002 ), jaguar ( Panthera onca ) ( Azevedo, 2004 ) and Puma yaguaroundii ( Rocha et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Ellenport (1981), the vesicular glands are absent in carnivores, a fact confirmed in the species studied because it presented as an accessory gland only in the prostate and the ampoule of the deferent duct. The absence of vesicular glands also described in domestic cats (Dyce et al, 2010) and in wild species as Puma yaguaroundii (Rocha et al, 2017).…”
Section: Discussionmentioning
confidence: 82%